BOLA KERANJANG SEBAGAI ALTERNATIF PEMBELAJARAN PENDIDIKAN JASMANI DISEKOLAH MENENGAH - Lilik Indriharta (Jurnal Pendidikan Jasmani Indonesia, 2006)
Korfball are the only game that involved man and women on each team. Nowadays peopleleft Korfball games as a sport in the high school. Although it offers many advantages: it’scheap, easy to play, simple equipment, and entertaining. High school age is a puberty age,a period in search of identity include they start to falling in love. Therefore, this game isgiving an appropriate timing to teach it in the high school. As a sport, Korfball requireddiscipline, teamwork, manners, sportsmanship and physical fitness. Therefore, sport teachercan use Korfball as alternative.Keyword: Bola Keranjang, Sport lesson.